How Lucrative & Challenging the Boundary less Opportunities for Data Scientists? - Sachin Kumar; P. S. Aitha, (International Journal of Case Studies in Business, IT and Education (IJCSBE), 2020)
The data scientist is a new profession which is considered as a key profession in the world of technologies and is one of the best paid jobs. A data scientist is a person who has developed expertise in the mathematical modelling and statistics that dominates programming and its different languages, computer science, and analytics. Data science comprises of data gathering, data warehousing, data analysis, data mining, online analytical processing, artificial intelligence, machine learning, and decision science for Predictive and prescriptive analytics for supporting managers for future decision process in a hectic competitive environment. Due to globalization and ICCT supported automation of many business processes, big data supported data science importance in many industries and hence Data scientists are also getting huge demand. Data scientists are key change-makers inside an enterprise that provides knowledge that they can illuminate the company's journey toward its ultimate business goals they have strong market demand. They are instrumental in inspiring both leaders and developers to build better products and paradigms. Their role in big business is becoming increasingly important, they are in ever shorter supply. Demand for data scientists is so exponentially growing that McKinsey expects a 50 percent difference in data scientists' supply versus demand by 2018. In this paper, we have analysed the continued opportunities for data scientists for 21st century business and how lucrative and challenging is their job based on opportunities and challenges framework.